Peran Guru Dalam Menciptakan Komunikasi Efektif Pada Anak Usia 4-5 Tahun - Pupung Puspa Ardini; Yenti Juniarti; Lowisa Yeblo (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
What is the role of the teacher in creating effective communication in early childhood 4-5 years at Ki Hadjar Dewantoro State Kindergarten, Kota Selatan District, Gorontalo City. Thesis Results of the Department of Teacher Education, Early Childhood Education, Faculty of Education, State University of Gorontalo. The formulation of the problem in this study is